Culture‐free biphasic approach for sensitive detection of Escherichia coli O157:H7 from beef samples. Issue 11 (26th August 2021) - Mostafa, Ariana; Ganguli, Anurup; Berger, Jacob; Rayabharam, Archith; Saavedra, Carlos; Aluru, Narayana R.; Bashir, Rashid
Abstract: Foodborne illnesses are a major threat to public health also leading to significant mortality and financial and reputational damage to industry. It is very important to detect pathogen presence in food products early, rapidly, and accurately to avoid potential outbreaks and economic loss. However, "gold standard" culture methods, including enrichment of pathogens, can take up to several days. Moreover, the food matrix often interferes with nucleic acid amplification methods of detection, requiring DNA extraction from the sample for successful molecular detection of pathogens. Here, we introduce a "biphasic" amplification method that can achieve high sensitivity detection with background noise from ground beef food samples without culture or other extraction methods in 2.5 h. Homogenized ground beef is dried resulting in an increase in porosity of the dried food matrix to allowing amplification enzymes and primers to access the target DNA and initiate the reaction within the dried food matrix. Using Loop Mediated Isothermal Amplification, we demonstrate the detection of 1–3 cfu of Escherichia coli bacteria in 30 mg of dried food matrix. Our approach significantly lowers the time to result to less than a few hours and have a pronounced impact on reduction of instrumentation complexity and costs. Abstract : Our novel biphasic LAMP approach demonstrates a culture‐free method for detection for low copy bacteria with high SNR with time to result in 2.5 hours.